Malthusian dynamics in a diverging Europe: Northern Italy 1650 - 1881 - Alan Fernihough (University College Dublin, UCD School of Economics, 2010)
Recent empirical research has questioned the validity of using Malthusian theory in pre-industrial England. Using real wage and vital rate data for the years 1650-1881, I provide empirical estimates for a different region - Northern Italy. The empirical methodology is theoretically underpinned by a simple Malthusian model, in which population, real wages and vital rates are determined endogenously. My findings strongly support the existence of a Malthusian economy where population growth depressed living standards, which in turn influenced vital rates. In addition, I find no evidence of Boserupian effects as increases in population failed to spur sustained technological growth.
hdl:10197/2671
Keywords: N33; J13; 330; Economic history; Demographic economics